2006
DOI: 10.1080/17402520600876796
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Redistribution of the Ro Autoantigen in Balb/c Mouse Like in Subacute Cutaneous Lupus Erythematosus

Abstract: In subacute cutaneous lupus eryhematosus (SCLE) the cutaneous antigens constitute the main source of Ro and La autoantigens. The aim of this investigation was to demonstrate if UV light increases the availability of Ro autoantigen in the skin, also the blocking effect of Ac-DEVD-CMK a caspase inhibitor was assessed. For this purpose newborn Balb/c mice were UVB irradiated (5–30 mJ/cm2) equivalent to a moderate to severe sunburn. Animals were injected with monoclonal anti-Ro antibodies from SCLE patients. Apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The Ac-DEVD-CMK peptide has previously been used in lupus experimental models to prevent apoptosis and tissue damage by antibody deposition [26, 27]. Here, we extend these previous observations to pemphigus and confirm the hypothesis that caspases inhibition can prevent blistering in pemphigus [10, 12, 13].…”
Section: Discussionsupporting
confidence: 86%
“…The Ac-DEVD-CMK peptide has previously been used in lupus experimental models to prevent apoptosis and tissue damage by antibody deposition [26, 27]. Here, we extend these previous observations to pemphigus and confirm the hypothesis that caspases inhibition can prevent blistering in pemphigus [10, 12, 13].…”
Section: Discussionsupporting
confidence: 86%
“…The stress induces changes of the cytoskeleton which is of particular importance because the actin-based cytoskeleton is a sensitive monitor of extra cellular stimuli (26,27). Is well established that stress increases the availability of intracellular antigens on cell surface, in consequence the autoantibodies trigger better antigens produced under cellular stress (28,29), present results confirm this notion, and suggest that the Ro and La redistribution is associated to the cytoskeleton modification; another interesting observation suggest that Ro and La suffer conformational changes and aggregates form transitory complexes with the cytoskeleton proteins through HSP70. As support to our Ro ad La proteins tagged another experimental model have been demonstrated that under UV irradiation Ro and La are shuttled to cell membrane associated to calreticulin and HSP proteins, the transport is executed by the cytoskeleton (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…46 These experiments demonstrated the pathogenic effects of anti-Ro antibodies, suggesting that antibody deposition induces ADCC cytotoxicity, leading to the inflammation and apoptosis of keratinocytes, which release intracellular Ro antigens, creating a pathophysiological loop. 47,48 The cardiac manifestations of NL include variable degrees of CHB, which is manifested as intrauterine bradycardia or low heart rates at birth. These anomalies persist for days or months, depending on the extent of the blockade, and when fibrosis of the atrial node is present, the blockage is permanent.…”
Section: Ro/ssa Molecular Complexmentioning
confidence: 99%